AGRO INDUSTRI KOPI RACIK (Studi Kasus Kelayakan Usaha pada Industri Kopi Racik X di Kota Kediri) - -, Darsono (MAPETA, 2000)
Background of racik coffee industry, was so much tide competition in packed coffee business.Therefore to get a coffee market, some proccessor try a form of coffee with spices ingredient. As ginger, curcume and so on, so that creted a form of coffee with special flavour. Beside that, racik coffee agroindustry cancreate demployment. The objective o this research are(1) to know feasibility of racik coffee agroindustry X in Kediri, (2) profit, and (3) absorbed labour. The result show that:(1) racik coffee aqroindustry X is feasible, RIC ratio is next two, (2) the profitis Rp. 173.4081 day, (3 ) it can absorb 16 labours